HIP ARTHROSCOPY VS. PHYSICAL THERAPY IN PATIENTS WITH FEMOROACETABULAR IMPINGEMENT: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS. Issue 4 (28th April 2020) - Schwabe, Maria; Cheng, Abby L; Pascual-Garrido, Cecilia; Harris-Hayes, Marcie; Harris, Michael; Hunt, Devyani; Prather, Heidi; Clohisy, John C; Nepple, Jeffrey J
Introduction: Both physical therapy (PT) and surgery appear to have some efficacy in treating femoroacetabular impingement (FAI). Only recently have high-level evidence studies compared these two options, though results of these randomized controlled trials (RCTs) are contradictory. The purpose of this study was to perform a systematic review and meta-analysis of RCTs comparing PT and surgery in patients with FAI. Methods: A systematic review was performed to identify randomized trials comparing FAI and PT. Data was extracted for demographics, study design, patient reported outcomes (PROs), and study quality/bias. In total, 819 abstracts were reviewed, with three RCTs identified (Griffin 2018, Mansell 2018, and Palmer 2019). All three RCTs reported iHOT-33, while two studies reported HOS ADL and Sport (Mansell 2019 and Palmer 2019). In a random effects meta-analysis, between-group differences in post-intervention scores were assessed using intention-to-treat analysis in each study. Results: All 3 RCTs reported PROs improvement from baseline to follow-up for both PT and surgery. The meta-analysis demonstrated greater improved iHOT-33 outcomes with surgery compared to PT with a mean relative difference of 11.3 (95% CI 1.86-20.73, p=0.014). The meta-analysis for HOS ADL and Sports (two RCTs) similarly demonstrated higher scores with surgery with a mean difference of 3.9 (95% CI -9.6-17.3, p=0.571) and 6.2 (95% CI -6.8-19.2, p=0.347), respectively, though without statistical significance. The quality of two RCTs was assessed as good with minimal bias (Griffin and Palmer). In the third RCT, an extremely high crossover rate may affect its validity (Mansell 2018, 70% crossover from PT to surgery). For instance, HOS ADL outcome based on treatment received, adjusting for Mansell's crossover rate, favored surgery with a larger mean difference of 12.0 (95% CI 7.5-16.5, p<0.001) (compared to intention-to-treat difference of 3.9). Discussion: In patients with FAI, combined results of three RCTs demonstrate superior outcomes of surgery compared to PT. However, PT can result in improvements in some patients and does not appear to compromise surgical outcomes. Provided that the studies adjusted for certain patient characteristics, further research needs to identify patient characteristics that predict success of non-operative and operative treatment of FAI in specific patient subgroups. : Figure 1. Mean Difference in iHOT-33 between Surgery and Physiotherapy